Evaluasi Komprehensif Teks Akademik Buku Ajar Bahasa Indonesia untuk Perguruan Tinggi Edisi Revisi 2024 - Muhammad Surip; Inka Fadila Damanik; Iriani Zakiah; Ruth Asri Febriani (Jurnal Bintang Pendidikan Indonesia, 2024)
The aim of this research is to describe rate scientific text academics in the text report results observation ( textbook Language Indonesia For college tall edition revised in 2024) is viewed based on simplicity structure and density information . This type of research is classified as research qualitative in descriptive form with techniques data collection uses technique documentation , engineering read , and note-taking techniques through sources written form text academic . As for sources the data obtained from Indonesian language textbook for College Edition Revised 2024. Presentation The results and data analysis in this research use approach linguistics systemic functional .Research result show that this textbook is successful serve various type text academic , incl text review , research and activity proposal text , text report research and activities, as well text article scientific , with a systematic structure and rich content . This book provides clear guide as well as relevant examples , helpful students understand, write , and analyze various type text academic . In conclusion , this textbook provides contribution significant to Indonesian language learning in college high and worthy made reference main . Suggestions are given For enhancement quality of material, improvement of text examples, use of interactive media , lecturer training , and collection feedback from users for repair sustainable.